TOD Zoning Planning: Floor Area Ratio Attenuation Rate and Center Migration Trajectory - Tiefeng Chai; Feng Lu; Jing Gao; Xin Deng; Rui Gao; Qingsong He (Land)
A Transit-Oriented Development (TOD) strategy aims to reshape the spatial structure of high-density cities by encouraging the development of functional compounding and centralizing development goals. As a primary planning model, TOD station areas are based on zones’ structure. Studies have confirmed, however, that the current land structure between zones displays a high degree of homogeneity. There are several issues shown here, such as blurred station boundaries, spatial confusion, and a deviation of the TOD center. Based on the corridor effect theory, differentiated distribution characteristics of land structural elements are determined between zones. To clarify the difference between station zones, this study uses the floor area ratio attenuation rate as its primary method. As well as measuring their changes, it also measures their trends. The purpose of this study is to investigate the interactive relationship between multiple elements in the station zoning planning process. Also, it aims to explore the endogenous relationship of the station area with its existing spatial characteristics. Accordingly, a zoning planning model of 200–400–700 m is proposed, which lays the foundation for future research on standards for boundary delineation and center migration trajectory rules for station area zones.